Review of external trade: Nigeria 1979 - Federal Offices of Statistics, Lagos (Lagos, Nigeria : Federal Office of Statistics, 1979)
This issue is the External Trade Review for Nigeria for 1979. Comparative figures are provided for 1975 - 1978.
osc 08/03/2019
Arch
Keywords: External trade; Nigeria